Mitigasi Agronomis Cekaman Kekeringan Dalam Produksi Tanaman Kentang (Solanum tuberosum L.) - Firdausy, Febrizany Sanjung Miftahul; Dora, Zelin Alsyah; Endrawan, Raka Teo; Amiati, Nani Tri; Indra, Zahra Salsabila; Suci, Yanuavitha Triana Eka; Tyara, Tyara; Almunawar, Said Agil; Agustin, Ferani; Santoso, Marwin; Hayati, Lena; Fahrurrozi, Fahrurrozi (University of Prof. Dr. Hazairin, SH, 2024)
Potato production is increasingly encountered with drought stress, which is one of the factors in affecting agricultural yields as a result of the dynamics of global climate change and the agricultural environment. Efforts to improve the ability of potatoes to adapt with drought stress could be done through plant breeding approaches and a combination of various agronomic practices. This review aims to describe the application of agronomic action strategies that can be used to improve the ability of potatoes to adapt to drought conditions. Various agronomic practices can be applied to mitigate the stressful potatoes to have maximum production grown under drought conditions. These mitigations include the use of drought tolerant varieties, selection of planting material, spacing, selection of the right planting time, providing shade, using organic and inorganic mulch, agricultural land management, weed and pest controls, cropping systems, row-planting orientations, using organic fertilizers and applying beneficial microorganisms.